Sítio Roberto Burle Marx's stonework / RJ - Haas, Yanara Costa (Anuário do Instituto de Geociências, 2012)
The aim of this paper is to inform the public Roberto Burle Marx's artistic works in landscape and stone work in the ancient Sítio Santo Antonio da Bica in Barra de Guaratiba/RJ. Researches of historic documents, interviews with friends and employees of the current Sítio Roberto Burle Marx beyond metric surveys and photographs were used to compose this work. Many discussions still may derive from the geological and the aesthetic concept of the modern use of demolitions stonework.